Anti‐β2‐glycoprotein I antibodies. (21st May 2013) - Willis, Rohan; Pierangeli, Silvia S.
Abstract : Anti‐β2 ‐glycoprotein I (anti‐β2 GPI) antibodies are the main antiphospholipid antibodies, along with anticardiolipin and lupus anticoagulant, that characterize the autoimmune disease antiphospholipid syndrome (APS). While the exact physiological functions of β2 GPI are unknown, there is overwhelming evidence that anti‐β2 GPI antibodies are pathogenic, contributing to thrombosis, pregnancy morbidity, and accelerated atherosclerosis in APS and systemic lupus erythematosus patients. The revelation that these antibodies play a central role in the pathogenesis and pathophysiology of APS has driven research to characterize the physiology and structure of β2 GPI as well as the pathogenic effects of anti‐β2 GPI antibodies. It has also resulted in the development of improved testing methodologies for detecting these antibodies. In this review we discuss the characteristics of β2 GPI; the generation, pathogenic effects, and standardized testing of anti‐β2 GPI antibodies; and the potential use of therapies that target the β2 GPI/ anti‐β2 GPI interaction in the treatment of APS.